The Role of Good Corporate Governance in Mitigating Financial Constraints - Elryanti; Satrio, Arif Budi (SAFE-Network, 2025)
Understanding the role of good corporate governance in mitigating financial constraints is increasingly urgent due to fluctuating capital market pressures. Access to external financing determines their ability to invest and ensure company sustainability. This study aims to analyze the role of corporate governance in the dynamics of funding access for companies in the non-primary consumer goods sector in Indonesia during the 2020-2024 period. Funding access reflects financial constraints using the SA Index as a proxy, while corporate governance is determined based on structural indicators and governance disclosure. The results of the regression modeling analysis indicate that companies with better governance tend to face lower funding constraints. This study concludes that governance plays a significant role in strengthening company credibility and reducing financing risks. These findings are useful as they can serve as a basis for companies and stakeholders in formulating more effective governance strategies and funding policies.